Automated classification of rubber seed clones using combination three different sensors with Arduino Uno / Siti Noor Ain Ismail - Ismail, Siti Noor Ain (2014)
This paper studies automated rubber seed clones using three different sensors with simple technology using application of Arduino Uno. There are five types of clones from the same species of rubber seed have been used as samples in this paper which are RRIM 2002, RRIM 2015, RRIM2020, RRIM2023 and RRIM2024. Also for each type, there are 30 samples taken. The three different sensors were arranged side by side around rubber seed, to ensure that all lateral surface samples taken the reading. Meanwhile, Arduino Uno has be used as a controlled to control this system. The one way ANOVA was used to analysis the data that converts from light reflectance of color by takes 30 samples readings from 5 difference clones. Then, error plot contracted by using data obtained in ANOVA. Error plot constructed in order to identify if there any overlapping between samples existed.